Problemas ontológico-políticos de la copia reproductible: consideraciones sobre la crítica de Hennion y Latour a Benjamin - Berti, Agustín (2020)
“Ontological-political Problems of the Reproducible Copy: Considerations on Hennion and Latour’s Critique of Benjamin”. This paper explores some ontological and political implications of the phenomenon of technical reproduction that takes place at the beginning of the 20th century. In philosophy of technology there is a basic agreement that social and political innovations cannot be understood independently from the emergence and use of certain technical means. Our objective in this work is to critically explore an aspect usually underestimated in this type of inquiry about technology: how inherently technical properties attached to certain new technical systems (for instance, reproduction systems) can actually favor some purposes and uses instead of others. With this objective, the paper reconstructs Walter Benjamin’s perspective on the problem of reproducible copies and discusses Latour and Hennion’s recent criticisms.